Difusi Inovasi Sedekah Melalui Tandan Sawit - Aswen, Latif; Sulastri, Irta; ., Hermawati (CV. ITTC INDONESIA, 2024)
This research aims to reveal new innovations in collecting alms through palm bunches in Asam Jujuhan District, Dharmasraya Regency. Collecting alms through palm bunches began with a program from the Dharmasraya Regency National Zakat Amil Agency (BAZNAS), which was related to increasing the collection of zakat, infaq and alms funds. To support this program, a new model for collecting alms was created, namely alms from palm bunches. Currently, alms through palm bunches is showing positive results. The research methodology used in this research is descriptive qualitative, using observation, interview and documentation data collection techniques. The research results show that collecting alms through palm bunches is very effective and the collection of alms funds at the National Zakat Amil Agency (BAZNAS) Dharmasraya Regency has increased.